The double homeobox a pseudogene 8 accelerates cell proliferation, migration, and invasion in colon cancer. Issue 4 (1st April 2022) - Mao, Shengxun; Mo, Zhaohong; Wu, Runxin; Lai, Bin; Zhou, Zhiyong; Song, Yi; Ouyang, Xi; Zhu, Xingen
ABSTRACT: Double homeobox A pseudogene 8 (DUXAP8) is a known tumor promoter in several malignancies. Nonetheless, its function in colon cancer (CC) is indefinite. Herein, we explored the significance of DUXAP8 and its underlying mechanism in CC. Our data indicated that DUXAP8 was upregulated in CC, and it was related to advanced stages and lymph node metastases. Based on our Kaplan-Meier survival analysis, elevated DUXAP8 expression resulted in shorter patient overall survival (OS). Conversely, DUXAP8 silencing strongly suppressed cellular proliferation, migration and invasion in vitro . Based on our western blot analysis, DUXAP8 deficiency strongly inhibited the epithelial–mesenchymal transition (EMT) in vitro . Alternately, DUXAP8 overexpression accelerated cellular proliferation migration and invasion in CC. Finally, silencing DUXAP8 prevented tumorigenesis in a mouse xenograft model in vivo . Collectively, our results demonstrated that DUXAP8 regulates the occurrence and advancement of CC, and may serve as a regulatory hub for this disease. Graphical abstract: uf0001